2020
DOI: 10.9734/jocamr/2020/v10i330164
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal Activity of Senna alata, Senna bicapsularis and Pityrogramma calomelanos

Abstract: Aims: Senna alata (Carrion crow bush), Senna bicapsularis (Money bush) and Pityrogramma calomelanos (Wild maran) are known for their value in traditional medicine. The study was an effort to identify, environment friendly antifungal compounds from these locally available plants against fungal pathogen Curvularia lunata. Study Design: An experiment based study done to identify antifungal property and phytochemical identification of C. lunata. Place and Duration of Study: Plants were collected from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…In Nigeria, Uwazie et al [17] and Oluwole et al [18] reported that the leaves, stem, and root are used to treat wound, skin diseases, respiratory tract infection, burns, diarrhoea and constipation. Its leaves are used against malaria pathogens [19,20,21,22], skin rashes and mycosis [9,23,24,25], diuretic and purgative [26], wound healing [27,28] and diarrhea [29]. The leaves, roots and stem-bark are also specific for the treatment of eczema [30].…”
Section: Introductionmentioning
confidence: 99%
“…In Nigeria, Uwazie et al [17] and Oluwole et al [18] reported that the leaves, stem, and root are used to treat wound, skin diseases, respiratory tract infection, burns, diarrhoea and constipation. Its leaves are used against malaria pathogens [19,20,21,22], skin rashes and mycosis [9,23,24,25], diuretic and purgative [26], wound healing [27,28] and diarrhea [29]. The leaves, roots and stem-bark are also specific for the treatment of eczema [30].…”
Section: Introductionmentioning
confidence: 99%